A comparison of rheokinetics on static and shear crosslinking processes of xanthan gum. Issue 6 (3rd June 2017) - Zhang, Hong; Lu, Yongjun; Fang, Bo; Qiu, Xiaohui; Zhai, Wen; Wang, Liwei; Jin, Hao; Li, Kejing
ABSTRACT: The crosslinking process of xanthan gum was studied under static and shear conditions. Conventional rotational rheometer was adopted to study the shear crosslinking process, and the static crosslinking process was monitored using an optical microrheometer without physical contact between the instrument and the sample. Both experiment and numerical simulation were adopted to compare the two gelation processes at different temperatures. The results showed that the effects of temperature on static and shear crosslinking processes of xanthan gum have the same trend and the rheological curves of the two gelation processes are similar in shape. The same rheokinetics equations were established to describe the two gelation processes and the simulated values are in good agreement with the experimental data. The changes of the model parameters with respect to temperature are quite similar for both the gelation processes, which verifies the feasibility of the microrheology method for measuring the static crosslinking reaction. GRAPHICAL ABSTRACT: Static and shear crosslinking processes of xanthan gum were studied by optical microrheology and classical rheology, respectively. Both experiment and numerical simulation were adopted to compare the two gelation processes. Good agreement was found when comparing the results obtained from microrheology to classical rheological measurements, which verifies the feasibility of the microrheology method for measuring the static crosslinking reaction.